An Exploratory Factor analysis Examining Psychological correlates among Females (Bangladesh Journal of Medical Science, 2023)
The working status of women provides them with a different psychological foundation than non-working women. Literature is evident that there is an immense difference between working and non-working women, especially the psychological factors affecting them.Objective: The aim of this study was to identify the difference between working and non-working women on the basis of psychological factors mainly quality of life, psychological well-being, self-esteem and perceived stress. Methods: Cross sectional research design was employed to measure the psychological factors of working and non-working women in the age group of 25 to 45 years. The sample size was recruited as 600 by power analysis, with 305 working and 295 non-working women. Data collection was conducted using WHO-QOL-BREf, Ryff’s Psychological well-being scale, Rosenberg’s Self-esteem scale and Cohen’s perceived stress scale. Data was analysed using descriptive statistics, independent T-test and factor analysis.Results: Findings of the study revealed that working women are higher on social and environmental quality of life and environmental mastery, positive relations with others and self-acceptance domains of psychological well-being than non-working women. The psychological variables are significantly correlated and significant factor loadings were for environmental mastery and social quality of life for working women and self-acceptance domain of psychological well-being, social and physical quality of life for non-working women.Conclusion: The results of this study suggest that there is a significant difference between working women and non-working women for the psychological correlates. In addition, the psychological variables are significantly influencing one another and the most effective influence is environmental mastery and social quality of life for working women and self-acceptance and social and physical quality of life for non-working women.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.106-115